Will they fit? Determinants of the adaptability of stock TMJ prostheses where custom TMJ prostheses were utilized. Issue 2 (February 2021) - Brown, Z.L.; Sarrami, S.; Perez, D.E.
Abstract: Currently only two alloplastic temporomandibular joint (TMJ) total joint replacement (TJR) systems are available in the United States. The aim of this study was to define variables that determine whether a Biomet stock prosthesis could have been used to reconstruct a TMJ previously reconstructed with a TMJ Concepts patient-fitted prosthesis. All of the TMJ Concepts prostheses placed between 2010 and 2018 at the University of Texas – Health at San Antonio were analyzed retrospectively. There were 128 cases (241 joints) with intact stereolithographic models analyzed for successful adaptation of the Biomet stock TMJ prosthesis. Anatomical, demographic, etiological, and perioperative data were gathered for each joint to investigate possible causes of failure of stock adaptation. The majority of joints, 74% (178/241), could have had a stock prosthesis adapt. All joints with ≥40 mm gap arthroplasty failed stock prosthesis adaptation. Only 50% (32/64) of the joints with at least one previous open TMJ surgery and 60% (58/96) of the joints with concomitant orthognathic surgery could have had a stock TMJ prosthesis. The stock prosthesis could not be adapted for any of the patients requiring TMJ replacement for congenital disorders or those requiring TMJ salvage. Overall, the majority of cases treated with a patient-specific TMJ TJR could have been treated with a stock prosthesis.